Anthropometry, body image, self-esteem and dietary quality of Brazilian female flamenco dancers. Antropometría, imagen corporal, autoestima y calidad de la dieta de brasileñas practicantes de baile flamenco - Ingrid Sayumi Nakamura; Claudia Ridel Juzwiak; Daniela Hummel de Almeida; Fábio Tadeu Montesano (Revista del Centro de Investigación Flamenco Telethusa)
The objectives of this study were to evaluate the nutritional profile, the body image perception and self-esteem of 17 Brazilian adult female flamenco dancers. The methods used were: Body Mass Index (BMI), fat percentage, waist circumference, the Stunkard Figure Rating Scale for body perception and the Rosemberg Scale for self-esteem. Food intake was classified by the Healthy Eating Index (HEI). The average values found were: age 39.2 ± 8.3 years, practice time of 16 ± 11.5 months and 2.2 ± 0.9 hours a week. Although the majority of women (76.5%) had an adequate BMI, 88.2% they showed a high percentage of fat. The BMI was related to the percentage of fat (r=0,681; IC [0.298-0.875]) and associated with the current silhouette (p=0.018). Even though all dancers had a high self-esteem, 64.7% were not satisfied with their body. Underreporting was identified in 41.2% of the cases and it was not related to self-esteem or BMI. According to the HEI, the diet of 88.2% was classified as healthy. It was concluded that the women correctly evaluate their BMI and, despite their high self-esteem, they are not fully satisfied with their body.Los objetivos de este estudio fueron evaluar el perfil nutricional, la percepción de la imagen corporal y la autoestima de 17 brasileñas adultas practicantes de flamenco. Los métodos utilizados fueron: índice de masa corporal (IMC), circunferencia abdominal y porcentaje de grasa corporal, la Escala de Siluetas de Stunkardt para la percepción corporal y la Escala de Rosemberg para la autoestima. La ingesta de alimentos fue clasificada según el Índice de Calidad de la Dieta (ICD). Los valores promedios encontrados fueron: edad de 39,2 ± 8,3 años, tiempo de practica de 16 ± 11,5 meses y 2,2 ± 0,9 horas/semanales. La mayoría (76,5%) fue clasificada como eutrófica, sin embargo 88,2% presentaron porcentaje de grasa elevado. El IMC está correlacionado con el porcentaje de grasa (r=0,681; IC [0,298-0,875]) y asociado a la silueta actual (p=0,018). Aunque todas las practicantes presentaron elevada autoestima, se encontró que 64,7% presentaron insatisfacción corporal. El consumo energético habitual fue subestimado en 41,2% de la muestra y no se correlacionó a la autoestima o al IMC. La dieta del 88,2% de la muestra fue calificada como sana según el ICD. Se concluyó que las mujeres se autoevalúan correctamente según el IMC y que, aunque presenten elevada autoestima, hay insatisfacción corporal.